2020
DOI: 10.1038/s41562-020-0928-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of the COVID-19 epidemic in Brazil

Abstract: OVID-19 is a severe acute respiratory infection (SARI) that emerged in early December 2019 in Wuhan, China 1. The outbreak was declared a public health emergency of international concern by the World Health Organization on 30 January 2020. COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an enveloped, single-stranded positive-sense RNA virus that belongs to the Betacoronavirus genus and Coronaviridae family 2. SARS-CoV-2 is closely related genetically to bat-derived SARS-like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
295
1
61

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(385 citation statements)
references
References 43 publications
28
295
1
61
Order By: Relevance
“…Among the 1014 confirmed cases of COVID-19, the proportion of males was higher than that of females (60 vs. 40%) and the male:female ratio was 1.5:1.0. Consistent with these findings, a Brazilian study reported that 57.5% of 67, 180 cases were males [31]. On the contrary, most of epidemiological reviews and meta-analysis studies reported comparable rates of COVID-19 between males and females, but males tended to have higher fatality and mortality rates than females [5,6,32].…”
Section: Allele Frequencies Of Abo Blood Groupsmentioning
confidence: 68%
“…Among the 1014 confirmed cases of COVID-19, the proportion of males was higher than that of females (60 vs. 40%) and the male:female ratio was 1.5:1.0. Consistent with these findings, a Brazilian study reported that 57.5% of 67, 180 cases were males [31]. On the contrary, most of epidemiological reviews and meta-analysis studies reported comparable rates of COVID-19 between males and females, but males tended to have higher fatality and mortality rates than females [5,6,32].…”
Section: Allele Frequencies Of Abo Blood Groupsmentioning
confidence: 68%
“…As evidenced by the high R0 in the provinces closest to the start of the pandemic, where prevention measures were weak and scarce, due to multiple social and political factors. Likewise, other Latin American countries with deficient health policies and lack of timely actions, such as Peru and Brazil, obtained a higher average transmission potential of 2.97 [43,44] and 3.1 [45,46], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, they looked at the regional and ethnic distribution of the hospitalized patients [15,16], age-sex structure and clinical characteristics such as co-morbidities and symptoms [14,15]. Souza et al [14] show that 65.5% of cases are patients over 50 years old. Moreover, they also find that 84% of the patients reported having at least one underlying condition.…”
Section: Discussionmentioning
confidence: 99%
“…The SIVEP-Gripe database provides detailed patient-level records for all individuals hospitalized with severe acute respiratory illness, including all suspected or confirmed cases of severe COVID-19 reported by both private and public sector healthcare institutions, from small rural hospitals to large metropolitan academic centres [13][14][15][16][17]. The records include the date of admission, date of onset of symptoms, state where the patient lives, state where they are being treated, and date of outcome (death or discharge), among other diagnosis related variables.…”
Section: Datamentioning
confidence: 99%